MORFOLOGI TANAH INCEPTISOL SETELAH DILAKUKAN PENAMBANGAN UNTUK BAHAN BAKU PEMBUATAN BATU BATA - E Efriandi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
The purpose of this study was to observe changes in soil morphology after mining for the brick industry. The study was carried out by observing four soil profiles. i.e. (1) soils that have never been mined (control); (2) soils that have been mined and left more than 10 years, (3) soils that have been mined and left for Â± 5 years, and (4) soils that have been mined and left between 1-3 years. The method used in this study was the observation of a complete profile (cross-section of soil) which aimed to collect primary data directly through field observations and the description of individual soil horizons. The implementation of this research consisted of three stages, i.e. soil survey, soil profile description, and collection of soil samples from soils that have never been mined and that have been mined for years. Results of this study showed changes in soil morphology after the soils were mined for years, i.e. yellowish-brown colour, granular structure, loose consistency, no rooting zone, and abrupt horizons. The Inceptisol soils that have been mined for brick making materials experienced changes of morphology and soil properties. Further studies on land rehabilitation technique need to be carried out for consideration in restoring post-mining lands.